Construct validity and reliability of the Brazilian version of Hypertension Knowledge-Level Scale - Mireille Janczyk Hereibi; Juliana Perez Arthur; Maria de Fátima Mantovani; Ângela Taís Mattei; Wendy Julia Mariano Viante; Carina Bortolato-Major (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To validate the construct and test the reliability of the Brazilian version of Hypertension Knowledge-Level Scale. Methods: Methodological research with 220 participants in a primary health care unit from Curitiba, Paraná. The data were collected with a social demographic questionnaire and the Brazilian version of the scale. The construct validity and reliability were assessed using Cronbach's Alpha, Pearson's Correlation and Analysis of Variance. The discriminant validity was verified comparing groups of people with hypertension and without, using T test. Results: Cronbach's Alpha was 0.74. The groups comparison showed that people with hypertension had better results (p<0,001). Pearson's Correlation showed that the questions measure different aspects of the same construct, justifying its organization in subdimensions. Conclusion: The Brazilian version of Hypertension Knowledge-Level Scale is a reliable instrument, which had its construct and criterion validated to measure knowledge about hypertension among Brazilian people. It can help health professionals with planning educative actions.